2009
DOI: 10.1016/j.na.2008.11.014
|View full text |Cite
|
Sign up to set email alerts
|

q-Hardy–Berndt type sums associated with q-Genocchi type zeta and q-l-functions

Abstract: a r t i c l e i n f o MSC: primary 11F20 11S80 secondary 30B40 11B68 11S40 30B50 44A05Keywords: q-Bernoulli numbers and polynomials q-Genocchi zeta q-l series p-adic interpolation function q-Dedekind type sums q-Hardy-Berndt type sums a b s t r a c tThe aim of this paper is to define new generating functions. By applying a derivative operator and the Mellin transformation to these generating functions, we define qanalogue of the Genocchi zeta function, q-analogue Hurwitz type Genocchi zeta function, and q-Geno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…By using p-adic q-Volkenborn integral, in [27] and [28], Kim defined p-adic q-Dedekind sums. In [49], [48], [52], [53], we defined q-Dedekind type sums, q-Hardy-Berndt type sums and p-adic q-Dedekind sums. By using same method, p-adic q-analogue of the sum T m (h, k) may be defined.…”
Section: Some Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using p-adic q-Volkenborn integral, in [27] and [28], Kim defined p-adic q-Dedekind sums. In [49], [48], [52], [53], we defined q-Dedekind type sums, q-Hardy-Berndt type sums and p-adic q-Dedekind sums. By using same method, p-adic q-analogue of the sum T m (h, k) may be defined.…”
Section: Some Applicationsmentioning
confidence: 99%
“…Some of them are given by 1, − 1 2 , 0, 1 4 , · · · , E n = 2 n E n ( 1 2 ) and E 2n = 0, (n ∈ N) cf. ( [28]- [37], [25], [39], [47], [53], [51]) and see also the references cited in each of these earlier works.…”
Section: Introduction Definitions and Notationsmentioning
confidence: 99%
“…Dedekind [13] introduced the sum (1.1) in connection with the modular properties of the Dedekind η-function and deduced from his reciprocity law 12hk s(h, k) + s(k, h) = h 2 − 3hk + k 2 + 1 (1.3) (see [2, p. 62] and [19, p. 148]). In later years several mathematicians generalized s(h, k) and showed that the generalized functions too satisfy a reciprocity law, see [1][2][3][4][5][7][8][9][10][11][12]14,16,18,[20][21][22][23] and the references given there. The first proof of (1.3) does not employ the theory of the Dedekind η-function is due to Rademacher [17].…”
Section: Introductionmentioning
confidence: 99%
“…Can et al [8] gave twisted versions of the Frobenius-Euler polynomials, Dedekind type sums related to the Frobenius-Euler functions, and corresponding reciprocity law. In [20], Simsek constructed generating functions of q-Hardy-Berndt type sums and q-HardyBerndt type sums attached to Dirichlet character. He gave some relations and related to these sums.…”
Section: Introductionmentioning
confidence: 99%
“…When α = 1, G n = G (1) n (0) are called the Genocchi numbers. The reader may refer to [31] as an important work focusing on the Genocchi polynomials and their relations with different areas.…”
mentioning
confidence: 99%